PENGARUH KONSENTRASI STARTER Acetobacter xylinum TERHADAP KETEBALAN DAN RENDEMEN SELULOSA Nata de Soya - Budiarti, Retni. S (Biospecies, 2008)
Soybean wasted water is the disposed water from the process of making soybean. During these years thewater produced by soybean production is disposed to the environments, it will cause stink smell and pollutethe environments. In order to solve this problem,the wasted water can be utilized to make Nata de Soya. Natade Soya is one of the food products resulting from bactria Acetobacter xylinum. Making Nata de Soya, themost important thing should be considered carefully the starter concentration of Acetobacter xylinum given towasted water. This research is purposed to find out the effect of concentration of Acetobacter xylinum on thefermentation of soybean wasted water in making Nata de Soya. The process of fermentation is carried out onplastic plate,29 cm lenght and 24 cm width sealed with pieces of newspaper. Fermentation is done on roomtemferature and for fourteen days. The result of the research shows that starter concentration of Acetobacterxylinum influences the cellulose rendement and the thickness of Nata de soya on 15% of starter concentrationof Acetobacter xylinum that produces average thickness 1,32 cm and average sellulosa rendement 22,2 gr/L.Key word : starter concentration of Acetobacter xylinum, Sellulosa rendement,Nata de Soya.